Circulating soluble endoglin modifies the inflammatory response in mice - Ruiz-Remolina, Laura (PLoS One, 2017)
Inflammation is associated with every health condition, and is an important component of many pathologies such as cardiovascular diseases. Circulating levels of soluble endoglin have been shown to be higher in the serum of patients with cardiovascular diseases with a significant inflammatory component. The aim of this study was to evaluate the implication of circulating soluble endoglin in the inflammatory response. For this purpose, a transgenic mouse expressing human soluble endoglin (sEng+) was employed, and three different inflammatory approaches were used to mimic inflammatory conditions in different tissues. This study shows that control sEng+ mice have a normal inflammatory state. The lung and kidney injury induced by the inflammatory agents was reduced in sEng+ mice, especially the intra-alveolar and kidney infiltrates, suggesting a possible reduction in inflammation induced by soluble endoglin. To deepen into this possible effect, the leukocyte number in the bronchoalveolar lavage and air pouch lavage was evaluated and a significant reduction of neutrophil infiltration in LPS-treated lungs and ischemic kidneys from sEng+ with respect to WT mice was observed. Additionally, the mechanisms through which soluble endoglin prevents inflammation were studied. We found that in sEng+ animals the increment of proinflammatory cytokines, TNFα, IL1β and IL6, induced by the inflammatory stimulus was reduced. Soluble endoglin also prevents the augmented adhesion molecules, ICAM, VCAM and E-selectin induced by the inflammatory stimulus. In addition, vascular permeability increased by inflammatory agents was also reduced by soluble endoglin. These results suggest that soluble endoglin modulates inflammatory-related diseases and open new perspectives leading to the development of novel and targeted approaches for the prevention and treatment of cardiovascular diseases.